Anticancer Potency of Dimethyl 2-(2-Hydroxy-2-Methoxypropilidine) Malonate in Kombucha - Opik Taupiqurrohman; Firman Rezaldi; Dina Amalia; Yani Suryani (UIN Sunan Gunung Djati Bandung, 2022)
Kombucha has an anticancer potency because it has dimethyl 2-(2-hydroxy-2-methoxypropilidine) malonate compound. The research aimed to verify the compound dimethyl 2-(2-hydroxy-2-methoxypropilidine) malonate as an anticancer with the in-silico method, namely the molecular docking approach, drug likeness profile, and ADMET test. The tools used were the PyRx, Discovery Studio Visualizer, Sanjeevini, and pkCSM. The research material consisted of 3D Dimethyl 2-(2-Hydroxy-2-Methoxypropilidine) Malonate and Epidermal Growth Factor Receptor (EGFR). The analysis showed Dimethyl 2-(2-Hydroxy-2-Methoxypropilidine) Malonate is safe for consumption and can suppress cancer cells.